1990
DOI: 10.1149/1.2086682
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Studies on Protective Thin Co3 O 4 and NiCo2 O 4 Films Prepared on Titanium by Spray Pyrolysis for Oxygen Evolution

Abstract: Electrochemical studies were done on thin Co304 and NiCo204 films on Ti by cyclic voltammetric and potentiostatic polarization techniques. The films were quite conductive and prevented the underlying surface from playing a harmful role during measurements. The results indicated the formation of a surface quasi-reversible redox couple, CoW/Co m, in KOH solution. The reaction order with respect to OH-ion concentration was found to be nearly 2. The Tafel slopes decreased with increasing KOH concentrations. NiCo20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(77 citation statements)
references
References 22 publications
6
70
0
1
Order By: Relevance
“…Later, the plate was washed with distilled water and dried with air. Then, Bi-PbO 2 /Ti was doped with Co 3 O 4 according to Singh et al [14]. 100 mL of 0.15 M Co(NO 3 ) 2 ·5H 2 O solution was sprayed to prepare Co 3 O 4 film.…”
Section: Preparation Of Co-bi-pbo 2 /Ti Anodementioning
confidence: 99%
See 1 more Smart Citation
“…Later, the plate was washed with distilled water and dried with air. Then, Bi-PbO 2 /Ti was doped with Co 3 O 4 according to Singh et al [14]. 100 mL of 0.15 M Co(NO 3 ) 2 ·5H 2 O solution was sprayed to prepare Co 3 O 4 film.…”
Section: Preparation Of Co-bi-pbo 2 /Ti Anodementioning
confidence: 99%
“…Iniesta et al [13] studied using electrochemical method to treat biorefractory solution with high phenol content-1000 ppm, with Bi-doped lead dioxide electrodes, Bi-PbO 2 /Ti electrodes. Singh et al [14] developed a kind of PbO 2 /Ti electrode doped with Co 3 O 4 to strengthen its stability. To study the influence of electrode materials on anodic oxidation efficiency, graphite anode and a kind of high O 2 evolution overpotential metal oxide anode, Co-Bi-PbO 2 /Ti anode, were used as electrodes, in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of spinel Co 3 O 4 has been the primary objective for material chemists [16,17]. In these reported articles, a range of synthesis routes to produce spinel Co 3 O 4 have been proposed, such as namely, the thermal decomposition of a solid cobalt nitrate (380 °C) [18], chemical spray pyrolysis (350–400 °C) [19,20], chemical vapour deposition (CVD, 550 °C) [21], and the traditional sol-gel method (above 260 °C) [22]. It is also reported that porous nanotubes of Co 3 O 4 can be synthesized by microemulsion method [23], and Co 3 O 4 nanorods can be achieved by tweaking traditional molten salt synthesis [24] and solvothermal method [25].…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt oxide [Co 3 O 4 ] is a good candidate as an anode material for lithium secondary batteries because of its good electrochemical capacity and high recharging rate [12]. Various synthetic routes have been developed for the preparation of Co 3 O 4 such as thermal deposition [13], chemical spray pyrolysis [14], chemical vapor deposition [6], pulsed laser deposition [15], and traditional sol-gel method [16]. These methods need a relatively high temperature, and it is difficult to obtain nanocrystalline Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%